Valuing teachers' work : new directions in teacher appraisal (Camberwell, Vic. : Australian Council for Educational Research, 1994)
This book is divided into three parts: Conceptual developments: models and approaches; Contextual developments: state, national and overseas policies; and Case studies of teacher appraisal evaluation.
Keywords: Education; Australia; Teachers; Teachers -- Rating of; Teachers -- Rating of -- Australia